Fundamentals of weed science - Zimdahl, Robert L. (Academic Press, an imprint of Elsevier, 2018)
Placing weed management in the larger context of weed research and science, this book presents information on the role, control and potential uses of weed plants. From the emergence and genetic foundation of weeds, to means of control and environmental impact, the book uses an ecological framework to explore the role of responsible and effective weed control in agriculture.